2011
DOI: 10.3727/096368910x557182
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of Rat Islet Viability during Transplantation: Validation of Pharmacological Approach to Induce VEGF Overexpression

Abstract: Delayed and insufficient revascularization during islet transplantation deprives islets of oxygen and nutrients, resulting in graft failure. Vascular endothelial growth factor (VEGF) could play a critical role in islet revascularization. We aimed to develop pharmacological strategies for VEGF overexpression in pancreatic islets using the iron chelator deferoxamine (DFO), thus avoiding obstacles or safety risks associated with gene therapy. Rat pancreatic islets were infected in vivo using an adenovirus (ADE) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 57 publications
1
10
0
Order By: Relevance
“…Previous studies showed improvements in islet function and vascularisation following ex vivo transfection with the human VEGF gene [ 14 ], [ 15 ]. However, numerous risks have been associated with gene transfer, including the short-term nature of gene therapy, the immune response, problems with viral vectors and the risk of carcinogenesis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies showed improvements in islet function and vascularisation following ex vivo transfection with the human VEGF gene [ 14 ], [ 15 ]. However, numerous risks have been associated with gene transfer, including the short-term nature of gene therapy, the immune response, problems with viral vectors and the risk of carcinogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, a pharmacological approach to increase VEGF expression may be more suitable for clinical application. We previously reported that pre-treatment of pancreatic islets with deferoxamine, an iron chelator already in clinical use, induced VEGF overexpression by activating the hypoxia inducible factor-1α (HIF-1α) pathway; this approach improved metabolic control in diabetic rats [ 14 ], [ 16 ]. However, long-term maintenance of graft function was not achieved, probably due to the stabilisation of HIF-1α, which triggers apoptosis at high concentrations [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…[29][30][31][32][33][34] The use of proangiogenic, degradable hydrogels through the combination of angiogenic growth factors (GFs), such as the plateletderived GF (PDGF-BB) and vascular endothelial GF (VEGF), and biomaterials is an attractive approach that has shown enhanced therapeutic effect over delivery of GF alone. [35][36][37][38] Given the importance of islet revascularization in graft efficacy, we sought to explore the potential use of proangiogenic hydrogels within PDMS scaffolds at an alternative transplant site.…”
mentioning
confidence: 99%
“…Based on clinical hepatic islet transplantations, 10,000 IEQ/kg is needed to reach normoglycaemia [ 1 ]. Unfortunately, it has been estimated that approximately 40% of the transplanted islets will die during the instant blood mediated inflammatory reaction (IBMIR) [ 23 ] and another 10 to 20% will die during vascularization [ 24 ]. These losses can be avoided when using a bioartificial pancreas.…”
Section: Discussionmentioning
confidence: 99%